(untitled) (Itinerarios Educativos, 2020)
This paper presents partial results of a research project aimed at studying the construction of the rights perspective in three secondary schools dealing with social inequality contexts in an intermediate city of the province of Córdoba. The present work addresses the senses conveyed by youngsters in relation to the practices institutionalized by schools as rights enhancers in the dynamic and complex process of constructing citizenship within a context of neoconservative re-emergence that dispute over senses about the rights perspective in schools. The practices of youngsters in student councils of three schools and the areas for school assemblies are analyzed so as to question how they strengthen and/or put a strain on the rights perspective taken on for institutional projects.